(untitled) (IAHS Medical Journal, 2023)
Background: Thyroid gland is the endocrine organ that secretes hormones namely, Triiodothyronine (T3) and Thyroxine hormone (T4). T3 and T4 are released in relation to the message of tropic hormone TSH, by the anterior pituitary. Absences as well as excess of thyroid hormones have harmful impacts on the overall health condition like physical and mental impediment. Poor intelligence leading to poor academic performance is frequently observed in hypothyroid children. The study was aimed to estimate serum T3, T4 and TSH levels of a group of school going children in urban area of Chattogram, Bangladesh. Materials and methods: This cross-sectional observational study was conducted among school going children (Age: 7-12 years) of Chattogram city between January, 2022 and June 2022. Chattogram based three schools were selected by convenient sampling. A total of 500 blood samples of children were collected and serum T3, T4 and TSH levels were measured. Estimation of T3 and T4 were done by Radioimmunoassay (RIA) and estimation of TSH was done by Immunoradiometric assay (IRMA) in the in Vitro laboratory. Results: Among 500 children, the estimated mean ±SD serum T3 hormone level was2.46±0.79 (Range: 1.27-5.51) nmol/L, mean ±SD serum T4 hormone level was 141.99±32.77 (Range: 86.21-239.05) nmol/L and mean ±SD serum TSH hormone level was 1.58±1.04 (Range: 0.30-3.02) mIU/L. Conclusion: Thyroid hormone status of the study group children was found within normal limits. However, regular screening of children is suggested to identify the subclinical and unreported clinical cases, so that theiroptimum growth and development are ensured. IAHS Medical Journal Vol 5(2), Dec 2022; 67-69